The Knowledge of Romani and School Readiness of Roma Children - Kyuchukov, Hristo; Samko, Milan; Kopcanova, Dagmar; Igov, Peter (East European Journal of Psycholinguistics, 2016)
The paper presents results from an international research project looking at Roma children between the ages of 3 and 6 years old. Thirty Roma children from Southwest Bulgaria and 30 Roma children from East Slovakia were tested with a psycholinguistic test in Romani language, measuring the knowledge of different grammatical categories. In most East European countries, the children are tested employing psychological/IQ tests in the official languages of the country and if the child does not understand the test task, because of a lack of knowledge in that language, s/he is deemed to have “light mental retardation”. The knowledge of the children on different grammatical categories in their mother tongue is not taken into account. For the first time in Europe, a psycholinguistic test was developed for measuring the knowledge in Romani (comprehension and production). Categories such as wh-questions, wh-complements, passive verbs, possessiveness, tense and aspect, learning new nouns and verbs are measured with newly developed test. The knowledge of the children is connected with two theories: the ecological theory of Ogbu (1978) and the integrative theory of child development (García Coll et al. 1996). Ogbu’s theory stresses the importance of the home culture in the development of the children and the theory of García Coll and her collaborators presents the home environment and the SES of the families as an important predictor for language development and school readiness of the minority/migrant children. References Bafekr, S. (1999) Schools and their undocumented Polish and “Romany Gypsy” pupils. International Journal of Educational Research, 31, 295-302. Bakalar, P. (2004) The IQ of Gypsies in Central Europe. The Mankind Quarterly, XLIV, (3&4), 291-300. Berko, J. (1958). The child’s learning of English morphology. Word, 14, 150-177. Bronfenbrenner U (1979). The ecology of human development: Experiments by nature and design. Cambridge, MA: Harvard University Press. Bronfenbrenner U (1986). Ecology of the family as a context for human development: Research perspectives. Developmental Psychology, 22, 723-742. Cvorovic, J. (2014) The Roma: A Balkan Underclass. Ulster: Ulster Institute for Social Research. Forget-Dubois, N., Lemelin, J.-P., Perusse, D., Tremblay, R. E. & Boivin, M. (2009). Early Child Language Mediates the Relation Between Home Environment and School Readiness. Child Development, 80 (3), 736-749. García Coll, C., Lamberty, G., Jenkins, R., McAdoo, H. P., Crnic, K., Wasik, B. H. and García, H. V. (1996) An Integrative Model for the Study of Developmental Competencies in Minority Children. Child Development, 67 (5), 1891-1914. Han, W.-J. (2006) Academic Achievements of Children in Immigrant Families. Educational Research and Review. 1 (8), 286-318. Hollo, L. (2006) Equality for Roma in Europe. A Roadmap for Action. Budapest: OSI Kezdi, G. and Kertesi, G. (2011) The Roma/non-Roma test score gap in Hungary. American Economic Review, 101 (3), 519-525. Kyuchukov, H (2006). Desegregation of Roma schools in Bulgaria. Sofia: SEGA Kyuchukov, H. (2014) Acquisition of Romani in a Bilingual Context. Psychology of Language and Communication, 18 (3), 211-225. Kyuchukov, H., Kaleja, M. & Samko, M. (2016) Roma parents as educators of their children. Intecultural education, 26 (5), 444-448. Neuman, S., & Marulis, L. M. (2010). The Effects of Vocabulary Intervention on Young Children’s Word Learning: A Meta-Analysis. Review of Educational Research, 80 (3), 300-335. Ogbu J. U. (1978). Minority Education and Caste: The American System in Cross-cultural Perspective. New York: Academic Press. Ogbu J. U. (1981). Origins of human competence: A cultural ecological perspective. Child Development, 52, 413-429. Ogbu, J. U. (1988). Cultural diversity and human development. In: D. Slaughter (Ed.), Black children and poverty: A developmental perspective. San Francisco: Jossey-Bass. 11-28. Parsons, Talcott. (1940). An Analytical Approach to the Theory of Social Stratification. American Journal of Sociology, 45 (6), 841-862. Roskos, K., & Neuman, S. (2005). The state of pre-kindergartens standard. Early Childhood Research Quarterly, 20, 125-145. Rushton, J. P. Cvorovic, J. and Bons, T. A. (2007). General mental ability in South Asians: Data from three Roma (Gypsy) communities in Serbia. Intelligence, 35(1), 1-12. Rydland, V. (2009). “Whow-when I was going to pretend drinking it tasted coke for real!” Second-language learners’ out-of-frame talk in peer pretend play: A developmental study from preschool to first grade. European Journal of Developmental Psychology, 6 (2), 190- 222. Tomasello, M. (2003). Constructing a Language: A Usage-Based Theory of Language Acquisition. Cambridge, MA: Harvard University Press.